METAFISIKA INFORMASI DALAM PERSPEKTIF PEMIKIRAN JEAN BAUDRILLARD: KONTEKSTUALISASINYA DENGAN PERTAUTAN MEDIA DAN POLITIK DI INDONESIA - Wikandaru, Reno (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2017)
The 21st century is the age of information. Information spreads through newspapers, magazines, television; and also scattered very massively over the internet. This paper was written for two reasons. First, people sometimes perceive information identical with truth. Second, the metaphysics of information is important to be discussed when it is associated with the phenomenon of media and politics in Indonesia. This paper analyses the metaphysics of information by 'disclosing' information structures that refer to Jean Baudrillard's thought. For Baudrillard, behind the phenomenon of information there are actually three elements at once, namely representation, manipulation, and simulation. The three elements above, influence each other. Real information is the result of the process of representation, ie the process of re-preserving reality and then transmitting that representation of reality to others. Manipulation also becomes an important element in information. According to Baudrillard, the element of simulation in this information is still closely related to the first element, namely representation. Baudrillard said that in the simulation, information will be actualized, meaning that it will be dramatized in a spectacular fashion, but at the same time kept away from communication, and reduced to a sign.